Pengaruh Beberapa Jenis Herbisida yang Diaplikasikan Berbeda Dosis Dan Waktu Terhadap Kualitas Benih Kedelai Di Musim Penghujan - Johan Riry (Jurnal Agrista, 2007)
The Influence of Various Kinds of Herbicide Applicated at Different Dosages and Times on Soybean Seed Quality in Rainy SeasonABSTRACT. The experiment was carried out to study the influence of various kinds of herbicide at different dosages and times on soybean seed quality in rainy season. The experimental was conducted at PT Syngenta, Cikampek, West Java. This experimental was arranged in the split-split plot based of randomized block design with 2 replications. The main plot was the time application consists of: R6, R7, and R8 phase. The sub-plot was the application doses of the herbicide that consists of: no herbicide, lower dosage, medium dosage, and higher dose. The response observed covers the seed’s water content at harvesting, seed’s viability, seed’s vigor, the percentage of winkle seed, the weight of 100 seeds and the yield per plot. The result shows that the application of paraquat at lower dose and at R7 nd R8 phase yielding the highest quality compared to any other treatment.